Three-dimensional structure of thermohaline staircases in the tropical north Atlantic and their effect on acoustic propagation - Bulters, Amy C. (Monterey, California. Naval Postgraduate School, 2012)
Under typical conditions in the subtropical thermocline double-diffusion occurs in the form of salt fingering (warm, salty fluid overlies cold, fresh fluid). The formation of staircases in the thermohaline structure of the ocean has been observed since the late 1960s, with recent field data collected within the tropical Atlantic displaying staircases with high-gradient interfaces characterized by a unique spatial orientation determined by background temperature and salinity. Competing theories have been proposed to explain the dynamics of these staircases; however, the origin of the staircases and the mechanism that controls final equilibrium remains poorly understood. This thesis examines staircase development in the tropical Atlantic. Incorporating double diffusion using the flux-gradient formulation of Radko and Smith, staircases are numerically simulated to resolve the controversial aspects of the staircase theories. The staircase simulations are critically evaluated against the C-SALT experiment observations, and the conditions for their formation and explanation of the fully equilibrated state are resolved and explained. The effect of acoustic propagation through the three-dimensional modeled staircases is evaluated to determine the impact of these large staircase areas on various frequencies and depths. Approved for public release; distribution is unlimited. Lieutenant, Royal Australian Navy http://archive.org/details/threedimensional1094527801